Хищные клещи-фитосейиды (Parasitiformes, Phytoseiidae) Лесостепи УССР. Сообщение I. Виды рода Amblyseius - Колодочка, Л.А. (Вестник зоологии, 1973)
Host plants are indicated for each of 14 species of the genus Amblyseius. Species of red spider mites together with which the carnivorous mites are met are also mentioned. The species A. major is found in the USSR for the first time. A. astutus, A. herbarius, A. khnzoriani, A. reductus, A. zwoelferi are new for the republic fauna.